Experience with anonymous interactions reduces intuitive cooperation. (December 2018) - McAuliffe, William; Forster, Daniel; Pedersen, Eric; McCullough, Michael
Abstract The Social Heuristics Hypothesis claims that cooperation is intuitive because it is positively reinforced in everyday life, where behaviour typically has reputational consequences1, 2 . Consequently, participants will cooperate in anonymous laboratory settings unless they either reflect on the one-shot nature of the interaction or learn through experience with such settings that cooperation does not promote self-interest. Experiments reveal that cognitive-processing manipulations (which increase reliance on either intuition or deliberation) indeed affect cooperation3, but may also introduce confounds4, 5 . Here, we elide the interpretation issues created by between-subjects designs in showing that people are less cooperative over time in laboratory paradigms in which cooperation cannot promote self-interest, but are just as cooperative over time in paradigms that have the potential to promote self-interest. Contrary to previous findings6, 7, we find that cooperation is equally intuitive for men and women: unilateral giving did not differ across gender at the first study session, and decreased equally for both genders across sessions. Reputational concerns reinforce the instinct to cooperate in social situations. McAuliffe et al. find that cooperative habits can be overturned in one-shot anonymous interactions, when people learn that defection will not damage their self-interest.